Great-power competition and conflict in the 21st century outside the Indo-Pacific and Europe - Cohen, Raphael S.; Treyger, Elina; Chindea, Irina A.; Curriden, Christian; Gunness, Kristen; Golins'ka, Christina; Kepe, Marta; Klein, Kurt; Rhoades, Ashley L.; Vest, Nathan ([Research report], 2023)
During the Barack Obama, Donald Trump, and Joe Biden administrations, the United States made countering the rise of China in the Indo-Pacific and, to a lesser extent, checking Russian revanchism in Europe core priorities of its national security strategy. Historically, however, great-power competition and conflict have taken place outside the theaters of core concern to the competing powers. This report-- the summary of a four-volume series--explores where and how the United States, China, and Russia may be competing for influence in these secondary theaters (Africa, the Middle East, and Latin America); where and why competition might turn into conflict; what form that conflict might take; and what implications the findings have for the U.S. government at large, the joint force, and the Department of the Air Force.